一体化硝化-部分反硝化-厌氧氨氧化深度脱氮的污水处理工艺 (2024)
本发明公开了一种一体化硝化-部分反硝化-厌氧氨氧化深度脱氮的污水处理工艺，所述工艺基于序批式生物反应器，在反应器内接种活性污泥，反应器运行周期包括第一次进水、微好氧反应、第二次进水、缺氧反应、沉淀、排水以及闲置过程，控制微好氧反应过程中DO浓度为0.2～0.5mg/L；第一次进水为高速活性污泥池处理后去除有机物的污水，第二次进水为未处理的污水，控制第一次进水与第二次进水的体积比为1:1～2:1。本发明采用交替微好氧/缺氧和分步进水策略将微好氧硝化和缺氧PDA集合到单一序批式生物反应器中，简化操作工艺的同时降低了工艺中曝气的能耗，充分利用城市污水中的有机物，实现城市污水的深度脱氮，脱氮效率高达94.5±1.1％。 The invention discloses an integrated nitrification-partial denitrification-anaerobic ammonia oxidation advanced denitrification sewage treatment process, the process is based on a sequencing batch bioreactor, activated sludge is inoculated in the reactor, and the operation cycle of the reactor comprises the processes of first water inlet, micro-aerobic reaction, second water inlet, anoxic reaction, precipitation, drainage and idling. The DO concentration in the micro-aerobic reaction process is controlled to be 0.2-0.5 mg/L; the first inlet water is sewage which is treated by a high-speed activated sludge tank and is subjected to organic matter removal, the second inlet water is untreated sewage, and the